A facile precursor route towards the synthesis of Fe1−xS@NC-rGO composite anode materials for high-performance lithium-ion batteries. Issue 6 (18th January 2023) - Zhan, Guanghao; Yan, Ruibo; Liao, Wenhua; Hu, Qianqian; Huang, Xiaoying
Abstract : By using an interface engineering technique, nanocomposites with a distinctive double carbon layer of protection were created, which exhibit outstanding charge and discharge performance and excellent long-term cycling stability. Abstract : Iron-based sulfides are considered promising anode materials for lithium-ion batteries (LIBs) due to their low cost and high theoretical specific capacities. However, low conductivity and dissolution of lithium polysulfides during the reaction hamper their practical applications. Herein, we firstly synthesized N-doped carbon-coated Fe1− x S (Fe1− x S@NC) sheets through vacuum pyrolysis of the precursor Fe1− x S(en)0.5 (en = ethylenediamine). Then Fe1− x S@NC-rGO composites (rGO = reduced graphene oxide) were prepared in which the Fe1− x S@NC sheets were anchored on the rGO. The performance of the composites as an anode material for LIBs has been investigated. It is found that coating N-doped C on Fe1− x S surfaces can improve the surface conductivity and electrochemical kinetics of Fe1− x S, which is beneficial for the conversion between lithium polysulfides and Fe1− x S. In addition, the coated N-doped C on the Fe1− x S sheets can serve as a barrier to direct contact between the electrolyte and the material, reducing the dissolution of polysulfides and preventing the loss of active ingredients. More importantly, the double protection of the N-doped C layer and the flexible rGO substrate minimizes the structural damage caused by the cyclic expansion of Fe1− x S@NC-rGO. As expected, Fe1− x S@NC-rGO exhibits good rate performance with a reversible capacity of 939.5 mA h g −1 after 1690 cycles at a current density of 1.0 A g −1, along with outstanding charge and discharge performance and excellent long-term cycling stability. This work shows that the introduction of NC coating and the rGO matrix into Fe1− x S would synergistically enhance the performance of Fe1− x S for LIBs and highlights the effectiveness of the synthetic strategy for double carbon-based materials-protected sulfides in developing superior LIB electrodes.